GM4OS - Farinati, Davide (2024)
Farinati, D., & Vanneschi, L. (2024). GM4OS: An Evolutionary Oversampling Approach for Imbalanced Binary Classification Tasks. In S. Smith, J. Correia, & C. Cintrano (Eds.), Applications of Evolutionary Computation: 27th European Conference, EvoApplications 2024, Held as Part of EvoStar 2024, Aberystwyth, UK, April 3–5, 2024, Proceedings, Part I (Vol. 1, pp. 68-82). (Lecture Notes in Computer Science; Vol. 14634). Springer Nature Switzerland AG. https://doi.org/10.1007/978-3-031-56852-7_5 --- This work was supported by national funds through FCT (Fundação para a Ciência e a Tecnologia), under the project - UIDB/04152/2020 - Centro de Investigação em Gestão de Informação (MagIC)/NOVA IMS.